Temptation by Immortality: Body as a Commodity and Resource - Rubavičius, Vytautas (Problemos, 2008)
The article deals with the idea and temptation of immortality as promoted by new genetic discoveries and various production of postmodern culture. Postmodernity is considered a recent stage of the development of capitalism system marked by decisive turn to the resources of the human body and life processes. In order to explain the peculiarities of this stage of capitalism’s development insights of K. Marx and M. Heidegger are brought in. These insights are generalized under the concepts of commodification and resourcification designating the main forces of capitalist expansion which may be called a genetic colonization. Thus postmodernity is characterized not only by commodification of culture, services, abilities and skills, but especially by the resourcification of genetic and life materials with the powerful instrument of patenting. Genetic discourse is considered to be a new world-view in which other discourses are correlating and supporting the notion of an evolutionary trend from homo sapiens to techno sapiens. This trend brings out new possibilities to transgress the limit imposed on human beings by the forces of nature – mortality. The author of this article arrives at a conclusion that, first, the temptation by immortality can be regarded as a version of modernist ideology of human liberation from various social and heavenly constraints which is supported by scientific genetic discourse, becoming a stimulating factor of postmodern cultural production. Secondly, that all the possibilities stemming from new genetic and biotech discoveries fall under the regulation of property relations thus making “immortality” - a temptation and brand - both an exceptional commodity and commodifying force.